Kejohanan Catur Cilik UiTM 2024: nurturing young minds through strategic play / Siti Zaharah Mohd Ruslan ... [et al.]. - Mohd Ruslan, Siti Zaharah; Yaacob, Nurul Aityqah; Zulkifle, Farizuwana Akma; Rusli, Nur Ida Aniza; Othman, Norlida (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Kejohanan Catur Cilik UiTM 2024 was successfully organized by the Department of Computer Science and Mathematics, College of Computing, Informatics & Mathematics, UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah, in collaboration with the Kuala Pilah District Education Office. The event aimed to cultivate interest and enhance chess-playing skills among primary school students aged 7 to 12 in Kuala Pilah. The championship was held on 26 October 2024 at Dewan Anjung, UiTM Kuala Pilah attracting 93 participants from 32 schools, including children of UiTM Negeri Sembilan staff from the Kuala Pilah, Seremban, and Rembau campuses. The event was supported by several sponsors and volunteers, fostering a competitive yet educational environment. It successfully met its objectives of nurturing young talents, promoting strategic thinking, and building self-confidence among participants.